2010
DOI: 10.1007/s10499-010-9390-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on immunological, physiological response, and hepatopancreatic metabolism of juvenile Chinese mitten crab Eriocheir sinensis

Abstract: The juvenile Chinese mitten crabs Eriocheir sinensis (1.40 ± 0.43 g) were cultured in water of 5.34 ± 0.43 (hypoxia, treatment group) and 21.02 ± 0.06 kPa (high dissolved oxygen (DO), control group) DO for 24 h, respectively. The total hemocyte counts (THC), the hyaline hemocyte counts were measured at 0 and 24 h in the treatment group, and superoxide dismutase (SOD) activity, concentrations of lactic acid and hemocyanin (Hc) in hemolymph and the metabolism of hepatopancreas (concentrations of glucose, total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Our results showed dietary supplementation of H. pluvialis had no significant effects on the activity of PO in the serum, which was in agreement with the findings in P. monodon (Supamattaya et al 2005). Moreover, Hc is the major protein in hemolymph of crustacean which plays an important role in oxygen transportation, immune and defence function (Zhang, Huang & Qin 2004;Pan & Jin 2008;Qiu et al 2011). In the present study, the higher contents of Hc were found on T3 and T4, which suggested that dietary H. pluvialis powder could enhance hemolymph immunocompetence of male E. sinensis.…”
Section: Antioxidant Capacity and Non-specific Immune Indicessupporting
confidence: 88%
See 4 more Smart Citations
“…Our results showed dietary supplementation of H. pluvialis had no significant effects on the activity of PO in the serum, which was in agreement with the findings in P. monodon (Supamattaya et al 2005). Moreover, Hc is the major protein in hemolymph of crustacean which plays an important role in oxygen transportation, immune and defence function (Zhang, Huang & Qin 2004;Pan & Jin 2008;Qiu et al 2011). In the present study, the higher contents of Hc were found on T3 and T4, which suggested that dietary H. pluvialis powder could enhance hemolymph immunocompetence of male E. sinensis.…”
Section: Antioxidant Capacity and Non-specific Immune Indicessupporting
confidence: 88%
“…Moreover, Hc is the major protein in hemolymph of crustacean which plays an important role in oxygen transportation, immune and defence function (Zhang, Huang & Qin ; Pan & Jin ; Qiu et al. ). In the present study, the higher contents of Hc were found on T3 and T4, which suggested that dietary H. pluvialis powder could enhance hemolymph immunocompetence of male E. sinensis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations